PROFESSIONAL “BURNOUT” AS AN URGENT PROBLEM OF PERSONNEL MANAGEMENT OF AVIATION ENTERPRISES - M. V. Erchova; S. D. Lobanov (Научный вестник МГТУ ГА, 2016)
The results of research of the "risks" in the professional conduct of aviation professionals, leading to professional burnout syndrome. Comparative analysis of the propensity for "burnout" among different categories of aviation personnel,is given, the category with a clear tendency to "burnout" is istentified and directions for prevention of this syndrome are suggested.